Public hedge funds - SUN, Lin (Institutional Knowledge at Singapore Management University, 2018)
Hedge funds managed by listed firms significantly under-perform funds managed by unlisted firms. The under-performance is more severe for funds with low manager deltas, poor governance, and no manager co-investment, or managed by firms whose prices are sensitive to earnings news. Notwithstanding the under-performance, listed asset management firms raise more capital, by growing existing funds and launching new funds post listing, and harvest greater fee revenues than do comparable unlisted firms. The results are consistent with the view that, for asset management firms, going public weakens the alignment between ownership, control, and investment capital, thereby engendering conflicts of interest.